2016
DOI: 10.1007/s12928-016-0380-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in incomplete stent apposition area caused by jailed struts after single stenting at left main bifurcation lesions: micro-CT analysis using a three-dimensional elastic bifurcated coronary artery model

Abstract: Stent struts protruding into ostial side branch called “jailed strut” at bifurcation lesions is a likely cause of thrombus formation. We aimed to investigate the influences of multiple kissing balloon inflation (KBI) for stent expansion, and stent platform design, respectively, on the reduction of incomplete stent apposition area (ISA area) caused by jailed struts at a side-branch ostium, using a three-dimensional elastic left main (LM) bifurcated coronary artery model. The referenced LM bifurcation angle data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
0
7
0
1
Order By: Relevance
“…In a clinical setting, there are no measures to guide two blades facing the calcification. However, we have shown that three-time repetition of delivery-balloon inflation for stent deployment increased the luminal cross-sectional area [ 28 , 29 ]. Repeating the cutting balloon inflation by changing the rotation of the cutting balloon catheter may change the direction of the blades and may be able to adjust two blades toward the calcification.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, there are no measures to guide two blades facing the calcification. However, we have shown that three-time repetition of delivery-balloon inflation for stent deployment increased the luminal cross-sectional area [ 28 , 29 ]. Repeating the cutting balloon inflation by changing the rotation of the cutting balloon catheter may change the direction of the blades and may be able to adjust two blades toward the calcification.…”
Section: Discussionmentioning
confidence: 99%
“…16 In fact, a previous bench test showed that the 2-link stent had a wider SB ostium and lower stent strut jail. 17 Furthermore, optical coherence tomography analysis showed that a lower number of links reduced the incidence of the link-connecting configuration. 18 For these reasons, a lower number of links may have improved the angiographic outcomes in the bifurcation lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The second guidewire was recrossed through a target stent cell in front of the SBO under visual guidance, and SB dilation was performed with a 3.0 × 15 mm semi-compliant balloon 3 times, each time for 20 s, balloon inflation pressure was 6 atm according to the compliance chart. KBI was then performed 3 times [12] for 20 s each using two 3.0 × 15 mm semi-compliant balloons with minimal overlapping [13] and balloon inflation pressures of 6 atm. The balloon diameters for KBI were determined by Finet's formula: 0.678 × (3.0 mm + 3.0 mm) = 4.02 mm [14].…”
Section: Methodsmentioning
confidence: 99%